Methods of leadership behavior in terms of organizational commitment from the point of view of supervisors in some directorates of education in Iraq (Journal of the College of Basic Education, 2024)
The current research aimed to identify the methods of leadership behavior and organizational commitment from the point of view of supervisors in some directorates of education in Iraq, and the research areas consisted of supervisors in some directorates of Iraqi education.At the headquarters of the directorates of education in Iraq, and the most prominent conclusions were the validity of the measures of leadership behavior methods and organizational commitment that the two researchers prepared in measuring the methods of leadership behavior and organizational commitment. Physical education teachers in some directorates of education in Iraq enjoyed a good amount of (leadership behavior, organizational commitment) There is a positive correlation between leadership behavior styles and organizational commitment from the point of view of supervisors in some education directorates in Baghdad, and the most prominent recommendations Taking advantage of the measures of leadership behavior methods and organizational commitment that the two researchers prepared in measuring the methods of leadership behavior and organizational commitment, generalizing the results of the current study to physical education teachers in Iraq, emphasizing the care of the elements of the administrative process and making them among the priorities of administrative work, as it is the pillar of success in the directorates of sports activity, Emphasizing the dimensions of leadership behavior methods because of their importance in shaping the sound qualities of physical education teachers that fit the prevailing values ​​in the sports comWorking to establish emotional commitment because it is based on the degree of the individual’s attachment to the school through feelings and work relationships, and the normative commitment in which the individual is linked through the school’s mission and goals, which leads to an increase in organizational commitment, as well as introducing administrators to their rights and obligations towards the school.munity